2022
DOI: 10.31635/ccschem.022.202201780
|View full text |Cite
|
Sign up to set email alerts
|

Nonheme Iron-Catalyzed Enantioselective cis -Dihydroxylation of Aliphatic Acrylates as Mimics of Rieske Dioxygenases

Abstract: Enantioselective cis-dihydroxylation of alkenes represents an ideal route to synthesize enantioenriched syn-2,3-dihydroxy esters that are important structural motifs in numerous biologically and pharmaceutically relevant molecules. Bioinspired nonheme iron-catalyzed enantioselective cis-dihydroxylation meets the requirement of the modern synthetic chemistry from atomic economy, green chemistry and sustainable development perspectives. However, nonheme iron-catalyzed enantioselective cis-dihydroxylation is much… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
1
4
2
Order By: Relevance
“…Based on the H 2 18 O experiments, the possibility of manganese­(III)-hydroperoxide and manganese­(III)-peroxysulfate as the reactive intermediate was ruled out since both manganese­(III)-hydroperoxide and manganese­(III)-peroxysulfate cannot exchange their oxygen atoms with water. This result is completely different from the previous reports on the asymmetric cis -dihydroxylation of olefins by non-heme iron complexes and H 2 O 2 , in which no 18 O-incorporation from H 2 18 O into the cis -dihydroxylation product was observed and the oxygen atoms in the cis -diol product were from the same molecule of H 2 O 2 . The result led the authors to propose an iron­(III)-hydroperoxide as the reactive intermediate …”
Section: Resultscontrasting
confidence: 83%
See 3 more Smart Citations
“…Based on the H 2 18 O experiments, the possibility of manganese­(III)-hydroperoxide and manganese­(III)-peroxysulfate as the reactive intermediate was ruled out since both manganese­(III)-hydroperoxide and manganese­(III)-peroxysulfate cannot exchange their oxygen atoms with water. This result is completely different from the previous reports on the asymmetric cis -dihydroxylation of olefins by non-heme iron complexes and H 2 O 2 , in which no 18 O-incorporation from H 2 18 O into the cis -dihydroxylation product was observed and the oxygen atoms in the cis -diol product were from the same molecule of H 2 O 2 . The result led the authors to propose an iron­(III)-hydroperoxide as the reactive intermediate …”
Section: Resultscontrasting
confidence: 83%
“…Then, other reaction parameters such as solvent, temperature, and oxidant loading were examined using C1 as the catalyst (Table , entries 6–15). It is shown that the property of the solvent has a great influence on the catalytic performance toward cis -dihydroxylation (Table , entries 6–10), and methanol afforded the optimal yield and enantioselectivity (Table , entry 6), which is similar to the previous reports on non-heme iron-catalyzed asymmetric cis -dihydroxylation of olefins . More effectively, lowering the reaction temperature was demonstrated to be helpful in improving both the yield and the enantioselectivity (Table , entries 11–13), and 72% yield and 88% ee were obtained when the temperature was lowered to −20 °C (Table , entry 13).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Inspired by the iron-dependent arene cis -dihydroxylating Rieske dioxygenases, synthetic nonheme iron complexes have been extensively explored as catalysts for the cis -dihydroxylation of olefins using hydrogen peroxide (H 2 O 2 ) as a terminal oxidant, to replace the toxic and expensive osmium (and related high-valent compounds with cis -dioxo groups) catalyzed cis -dihydroxylation of olefins . As a result, several landmark discoveries, pioneered by Que, Che, and Costas, were observed in the nonheme iron-catalyzed (asymmetric) cis -dihydroxylation of olefins by H 2 O 2 . Regarding the cis -dihydroxylating intermediate, an iron(V)-oxo-hydroxo (HO-Fe V O) species, which is the product of the O–O bond heterolysis of an iron(III)-hydroperoxo intermediate, has been proposed as the active cis -dihydroxylating intermediate responsible for the cis -dihydroxylation of olefins in biomimetic systems (Figure S1b); ,,, in several cases, other iron–oxygen intermediates, such as iron(III)-superoxo and iron(III)-hydroperoxo, have been proposed as a potent oxidant in the cis -dihydroxylation reactions. ,, Accordingly, reaction mechanisms were proposed with an assumption that an HO-Fe V O species is the cis -dihydroxylating intermediate that reacts with olefins to yield cis -diols (Figure S1b). However, it should be noted that such an HO-Fe V O species has never been detected in any catalytic cis -dihydroxylation reactions and that the cis -dihydroxylation of olefins has never been attempted with isolated HO-Fe V O species.…”
mentioning
confidence: 99%